Pathologic-radiologic correlations in screen-detected ductal carcinoma in situ of the breast: Findings of the Singapore breast screening project - Tan, P.H. (2012)
10.1002/1097-0215(20000820)90:4<231::AID-IJC6>3.0.CO;2-U